VULVOVAGINAL TUBERCULOSIS IN AN INFANT: A CASE REPORT - Corimanya, Jorge (2015)
Objective: To present a case of vulvovaginal tuberculosis in an infant with vaginal bleeding. Setting: Children’s Health Specialized Institute. Patient: A 7-month girl with vulvovaginal and sistemic tuberculosis who was diagnosed by clinical and histopatological evidence. Case report: Infiltrative tumor of external genitalia, including vulva and vagina, accompanying generalized sepsis. Exam and incisional biopsy of the vaginal and clitoral lesion were performed under anesthesia with histopathological finding of genital tuberculosis, BAAR positive. The patient died due to systemic tuberculosis derived complications. Conclusion: Although uncommon, vulvovaginal tuberculosis should be suspected in cases of vaginal tumors, especially in developing countries with high prevalence of tuberculosis.